Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1007/s00268-019-05360-w
|View full text |Cite
|
Sign up to set email alerts
|

Foley Balloon Facilitates Creation of Working Space in Transoral Thyroidectomy

Abstract: Background Transoral thyroidectomy via the vestibular approach retains no scars in the body surface and is a good option for patients indicated for thyroidectomy but with cosmetic concerns. However, the working space of this procedure is relatively small and is also difficult to create compared with that of other remote‐access thyroidectomy procedures. Methods In this study, we first created a tract from the chin to the sternal notch, after which a Foley catheter with stylet was inserted through the middle ora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…Although TOETVA has many advantages compared to other thyroidectomy approaches, there are some initial difficulties faced by inexperienced surgeons including unfamiliarity with the cranio-caudal view and the use of laparoscopic instruments (21). Working space formation in TOETVA is an especially difficult procedure with a steep learning curve for inexperienced surgeons (10). Due to the limited field-of-view and small space, bleeding is difficult to control once it occurs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although TOETVA has many advantages compared to other thyroidectomy approaches, there are some initial difficulties faced by inexperienced surgeons including unfamiliarity with the cranio-caudal view and the use of laparoscopic instruments (21). Working space formation in TOETVA is an especially difficult procedure with a steep learning curve for inexperienced surgeons (10). Due to the limited field-of-view and small space, bleeding is difficult to control once it occurs.…”
Section: Discussionmentioning
confidence: 99%
“…Balloon dilators are especially popular for laparoscopic totally extra-peritoneal inguinal hernia repair because they enable easy dissection of the correct plane, resulting in better exposure and bloodless surgery with reduced operation time, conversion rates, and complications (7,24). Liang et al (10) reported the use of the Foley catheter balloon to create a working space in TOETVA, and concluded that Foley balloon dilatation helps overcome the difficulties of initial working space formation. Bertelli et al (9) later reported the use of the same Spacemaker balloon dilator for working space formation in TOETVA as we used in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Transoral endoscopic thyroidectomy was performed as described by Anuwong et al with a modification in the step of working space creation [ 13 ]. We applied the Foley balloon to dilate the subplatysmal space so as to minimize the use of blunt dissection and its associated injury [ 14 ]. The details of the perioperative management have been delineated in our previous publication [ 15 ].…”
Section: Methodsmentioning
confidence: 99%
“…Balloon dilatation with a balloon in the Foley catheter [ 50 ], cuff in the endotracheal tube [ 51 ], and commercialized balloon dilator device [ 47 , 52 ] are also alternative options used by some surgeons. With the balloon inflation pressure, it is easier to create a homogenous space with a clear tissue plane and achieve good hemostasis [ 50 ].…”
Section: Operative Techniquesmentioning
confidence: 99%